2023
DOI: 10.3390/ijms241210106
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pioglitazone Treatment Has No Significant Impact on Microglial Activation and Tau Pathology in P301S Mice

Abstract: Neuroinflammation is one disease hallmark on the road to neurodegeneration in primary tauopathies. Thus, immunomodulation might be a suitable treatment strategy to delay or even prevent the occurrence of symptoms and thus relieve the burden for patients and caregivers. In recent years, the peroxisome proliferator-activated receptor γ (PPARγ) has received increasing attention as it is immediately involved in the regulation of the immune system and can be targeted by the anti-diabetic drug pioglitazone. Previous… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…In a real-world study, TZD users were also found to have a significantly lower risk of developing various types of dementia compared to non-TZD users who received dual oral therapy [ 41 ]. At the same time, it is worth noting that a relatively small proportion of clinical and laboratory evidence on the efficacy of TZDs in treating AD currently shows mixed or neutral effects, suggesting that caution is needed when extrapolating our findings [ [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%
“…In a real-world study, TZD users were also found to have a significantly lower risk of developing various types of dementia compared to non-TZD users who received dual oral therapy [ 41 ]. At the same time, it is worth noting that a relatively small proportion of clinical and laboratory evidence on the efficacy of TZDs in treating AD currently shows mixed or neutral effects, suggesting that caution is needed when extrapolating our findings [ [42] , [43] , [44] ].…”
Section: Discussionmentioning
confidence: 99%
“…Another molecular mechanism through which PGZ works is the regulation of AKT/GSK3β activation, resulting in improved peripheral and central insulin sensitivity, increased Aβ42 degradation, and decreased Aβ accumulation in diet-induced insulin resistance rats [135]. Conversely, a study in which P301S mice used as tauopathy models were treated with either PGZ or placebo over 6 months showed us that PGZ only altered the time course of microglial activation but did not significantly affect microglial activation in response to tau [136]. A pilot study conducted in AD and MCI participants with T2DM improved both the cognition and metabolic profile of the participants in the PGZ group [137].…”
Section: Ppar-γ Agonistsmentioning
confidence: 99%